[OP.LB.02.02] NEUROMODULATION IN HYPERTENSION. (September 2016) - Nechutova, H.; Soucek, M.; Brabencova, K.; Stepanova, R.; Blaha, M.; Vanicek, J.
Abstract : Objective: In our study, we focus on particular brain neurons and their axonal connections within the brainstem and spinal cord, which regulate the sympathetic and parasympathetic nerves[Combining Acute Accent] functions, involved in the regulation of blood pressure. Processes of neuromodulation are mentioned to take place within these neural connections of central nervous system. The target group for analysis is represented by patients with hypertension. Design and method: We analysed the descending nervous fascicle in patients with hypertension and in healthy controls. All probands (16 patients with hypertension, 12 healthy controls) of our pilot study underwent the non-invasive, one-time magnetic resonance imaging scanning. For the central nervous system structures mapping, we[Combining Acute Accent]ve used the non-invasive Magnetic Resonance imaging techniques (3T MR system Discovery MR750 GE, software DV24.0_R01_1344.a), combined with specific software processing (Philips working station, MR Diffusion + MR FiberTrack analysis). Received data were analyzed by using statistics (Mann-Whitney test for comparison of parameters between groups). Results: For the oral presentation, the results are presented as very visual MRI – tractography images and clear Gauss[Combining Acute Accent] curves comparisons too. Figure. No caption available. Conclusions: There is a statistically significant difference in volume parametres of followed nervous fascicle, in patients with hypertension and healthy controls. Processes of neuromodulation are very likely to be taking place within the nerve tract in brain, which regulate the autonomic nervous system and thus control the blood pressure.